1984
DOI: 10.3109/13813458409071137
|View full text |Cite
|
Sign up to set email alerts
|

Effects of electrical stimulationin vivoofM. pectoralison carbohydrate metabolism with to certain liver and blood values in the pigeon

Abstract: The pectoralis muscles of two groups of anaesthetized pigeons were exercised in vivo by electrical stimulation for periods of 1 h and 5 h respectively. There was no significant change from controls in the level of blood glucose in both groups. Blood lactate level was significantly higher in the exercised groups but was relatively lower in the 5-h control group in comparison with its 1-h counter part. Blood lactate dehydrogenase (LDH) activity was significantly higher in the 1-h stimulated pigeons as was also t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

1987
1987
1993
1993

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Earlier biochemical and histochemical studies on pigeons had shown that during forced flight or electrical stimulation of the pectoralis muscle, carbohydrates were initially used as fuel and then fat as the major source of energy for prolonged muscular activity (George and Berger 1966;Vallyathan, Grinyer and George 1970;John and George 1973;McKeown, John and George 1974;Parker and George 1974;l975;Pilo et al 1984). A similar conclusion was arrived at by Butler, West and Jones (1977) from their study of the respiratory exchange ratio in pigeons flying in a wind tunnel.…”
Section: Discussionmentioning
confidence: 77%
See 4 more Smart Citations
“…Earlier biochemical and histochemical studies on pigeons had shown that during forced flight or electrical stimulation of the pectoralis muscle, carbohydrates were initially used as fuel and then fat as the major source of energy for prolonged muscular activity (George and Berger 1966;Vallyathan, Grinyer and George 1970;John and George 1973;McKeown, John and George 1974;Parker and George 1974;l975;Pilo et al 1984). A similar conclusion was arrived at by Butler, West and Jones (1977) from their study of the respiratory exchange ratio in pigeons flying in a wind tunnel.…”
Section: Discussionmentioning
confidence: 77%
“…However, the magnitude of the increase in lactate levels obtained by Butler, West and Jones (1977) in pigeons at the end of a 6 min flight in the wind tunnel, was much higher than the 60-80 min flight increase observed in the present study. In experiments with electrical stimulation of the pectoralis muscle in pigeons, blood lactate level was significantly high after 1 h stimulation but was much reduced after 5 h stimulation (Pilo et al 1984). These observations suggest that in prolonged muscular activity lactate produc- tion is considerably reduced because the muscle would be metabolizing mainly fatty acids.…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations